Family Christmas Photograph at Home - Watkins, Howard::::::::: (1983)
Howard Watkins, Christine Watkins holding Robin Watkins, Rose Watkins wearing Rambling Rose T-shirt, Albert Watkins, Adam Watkins, Frances Kamp Christmas tree in background with Howard's handmade ornaments